Results of the introduction of the promising ethnomedicinal plant Ferula tadshikorum in the Tashkent Botanical Garden and technology of resin production under different conditions - Khamraeva, Dilovar T.; Khojimatov , Olim; Mustafaev, Ilyor; Bussmann, Rainer W.; Sharipov, Abdinazar; Khalkuzieva, Mokhira; Rakhimova, Nargiza (Ethnobotany Research and Applications, 2025)
Background: The article presents the results of F. tadshikorum Pimenov introduction in Tashkent Botanical Garden and the technology of obtaining gum resin of roots from different growing conditions. Methods: To study ontogenesis and to distinguish age states of F. tadshikorum, generally accepted methods were used. Field studies in natural conditions were carried out by route methods based on observation. The timing of resin collection, technical methods of root pruning and the weight of gum resin obtained from one plant were studied. Results: According to the results of introduction in the Tashkent Botanical Garden the introduction evaluation of F. tadshikorum was carried out. Comparative data of conducted measures, time, technology of collection of gum resin from roots of F. tadshikorum were given. Climatic factors in natural populations and conditions of introduction were considered, the age of plants, time of collection, methods of root cutting were determined. The possibility of obtaining gum resin from virginile age specimens grown in the conditions of the Tashkent Botanical Garden in the sixth year of vegetation was established. In the conditions of Arnasay district of Jizzak region in the 10th year of vegetation, and in natural conditions plants of 12-16 years of life are mainly used. The yield of gum resin obtained from one plant was determined for plants from different locations, which makes it possible to calculate the economic efficiency of the plantations. Conclusions: The results of 6-year work on introduction of F. tadshikorum in conditions of Tashkent botanical garden are summarized and introduction evaluation is given. On the plantations created in Tashkent region, it is recommended to collect gum resin from virginile plants on the sixth vegetation season. Keywords: Afghan knife, Ferula tadshikorum, gum resin, introduction assessment, plantations, root.